The aftermath of COVID-19: generalized anxiety disorder and burnout among radiology practitioners and interns in Saudi Arabia - Alshamrani, Khalid M.; Alkenawi, Abdulkader A.; Falatah, Hebah A.; Alsulami, Waad; Alzahrani, Faisal A.; Nayta, Tariq M.; Alharbi, Abdulrahman H.; Alzahrani, Mohannad A.; Almutairi, Rahaf H.; Alshomrani, Bander S.; Tasslaq, Sameer E.; Aldhebaib, Ali M. (Frontiers in Psychiatry, 2024)
Background: The coronavirus disease (COVID-19) pandemic has presented unprecedented stressors and difficulties for healthcare professionals. This study explored the prevalence of generalized anxiety disorders and burnout among radiology practitioners and interns in various hospitals in Saudi Arabia after the end of the COVID-19 global public health emergency. Methods: A cross-sectional survey of 230 radiology practitioners and interns was conducted between October and November 2023. This study utilized the Generalized Anxiety Disorder 7-item (GAD-7) scale and Maslach Burnout Inventory-Human Services Survey for Medical Personnel (MBI-HSS-MP) 22-item questionnaire, employing a non-probability convenience sampling method. The average scores of the individual components constituting the GAD-7 scale and each burnout scale were calculated, and statistical analyses were conducted using the Mann-Whitney U and Kruskal-Wallis H nonparametric tests. Results: Of 382 radiology practitioners and interns, 230 (60.2%) responded to the survey. Notably, 42.6% of the participants reported experiencing GAD. Regarding burnout, 82.3% were at moderate-to-high risk for emotional exhaustion, 93.5% for depersonalization, and 52.1% for personal achievement. The 31–40 years age group showed significantly higher burnout rates (p = 0.001) compared with the other age groups. Those with more than three years of experience had notably higher emotional exhaustion scores (p = 0.002) and a nearly significant increase in depersonalization scores (p = 0.051) than those with less experience. Discussion: Our study revealed that 42.6% of radiology practitioners and interns experienced GAD, with the majority facing significant burnout. Furthermore, our research indicates a decline in GAD levels among radiology practitioners and interns compared with the peak COVID-19 pandemic period. It also showed a significant increase in both the incidence and severity of burnout, surpassing pre-pandemic levels in a comparable cohort. These findings emphasize the pressing challenges of GAD and burnout among healthcare workers, especially radiology professionals.